Arpu Kuilpu: An H5 from the outer main belt. (25th April 2022) - Shober, Patrick M.; Devillepoix, Hadrien A. R.; Sansom, Eleanor K.; Towner, Martin C.; Cupák, Martin; Anderson, Seamus L.; Benedix, Gretchen; Forman, Lucy; Bland, Phil A.; Howie, Robert M.; Hartig, Benjamin A. D.; Laubenstein, Matthias; et al.
Abstract: On June 1, 2019, just before 7:30 p.m. local time, the Desert Fireball Network (DFN) detected a −9.3 magnitude fireball over South Australia near the Western Australia border. The event was observed by six fireball observatories, and lasted for 5 s. One station was nearly directly underneath the trajectory, greatly constraining the trajectory solution. This trajectory's backward numerical integrations indicate that the object originated from the outer main belt with a semimajor axis of 2.75 au. A light curve was also extracted and showed that the body experienced very little fragmentation during its atmospheric passage. A search campaign was conducted with several DFN team members and other volunteers. One 42 g fragment was recovered within the predicted fall area based on the dark flight model. Based on measurements of short‐lived radionuclides, the fragment was confirmed to be a fresh fall. The meteorite, Arpu Kuilpu, has been classified as an H5 ordinary chondrite. This marks the fifth fall recovered in Australia by the DFN, and the smallest meteoroid (≃2 kg) to ever survive entry and be recovered as a meteorite.